Performance in Grain Yield and Physiological Traits of Rice in the Yangtze River Basin of China During the Last 60 yr - Hao ZHANG; Ting-ting CHEN; Li-jun LIU; Zhi-qin WANG; Jian-chang YANG; Jian-hua ZHANG (Journal of Integrative Agriculture, 2013)
Knowledge on the performance in grain yield and physiological traits is essential to understand the main yield-limiting factor and make strategies for breeding and crop management in rice (Oryza sativa L.). This study investigated the changes in grain yield and associated physiological traits of rice in the Yangtze River Basin of China during the last 60 yr. Thirteen mid-season indica and 12 japonica rice cultivars that were popularly used were grown in the field in 2008 and 2009. The grain yield and yield components, biomass, leaf area, leaf photosynthesis, root oxidation activity, and harvest index were examined. The results showed that grain yield and grain yield per day have progressively increased during the years and such increases are mainly attributed to the expanded sink size as a result of more spikelets per panicle, especially for the case of super rice. Both biomass and harvest index were increased with the improvement of cultivars. Increase in biomass for modern rice cultivars was associated with an enhancement of leaf area and photosynthesis, root dry weight, and root oxidation activity, although the indica super rice cultivars showed a lower leaf photosynthetic rate and root oxidation activity than the semi-dwarf cultivars during the grain filling period. Both indica and japonica super rice cultivars exhibited a low percentage of filled grains, which may limit their great yield potential. All the data suggested that grain yield have been substantially improved during the 60 yr of rice breeding in the Yangtze River Basin. Expanded sink size, increased dry matter production and harvest index, and enhanced leaf area and photosynthesis, root dry weight, and root oxidation activity contribute to the improvement in grain yield. Increase in filling efficiency could realize the great yield potential in super rice.